Evaluation of phenolic compounds as cross-linkers to improve the qualities of halal gelatin from milkfish scales (Chanos chanos) - Hamzah, Nursalam; Ibrahim, Slamet; Tjahjono, Daryono H. (Narra Sains Indonesia, 2024)
Gelatin is a versatile substance extensively used in medical and pharmaceutical industries for many applications, including capsule shells, X-ray film, infusion for plasma substitute, and the fabricating of artificial tissue. Fish scale gelatin is a profitable alternative source as a halal material despite its inferior quality. An addition of phenolic cross-linker may enhance the qualities of fish scale gelatin. The aim of this study was to determine the ability of phenolics to act as cross-linkers for fish scale gelatin and to identify the factors affecting this process. Gelatin production from fish scales (Chanos chanos) was carried out through basic pre-extraction and acidic pre-extraction. Thereafter, the gelatin was reacted with 10 different phenolics (phenol, pyrocatechol, resorcinol, α-naphthol, vanillin, L-tyrosine, curcumin, gallic acid, quercetin, and tannic acid). The resultant gelatins were characterized by infrared spectrum, X-ray diffraction pattern, swelling index, degree of cross-linking, viscosity, gel strength, mechanical profile, thermal profile, and water vapor permeability. Gelatin with the most favorable characteristics was further investigated for the effects of acidity (pH 4, 7, and 10) and cross-linker concentrations (2.5–10%). The findings revealed the formation of cross-linkage through shifted vibrational peaks of amide A, amide B, and amide II in the infrared spectrum. Shifted X-ray diffraction peaks in the gelatin with phenol addition also indicated the formation of cross-linkage. Significant improvement in the gelatin characteristics, such as swelling index, degree of cross-linking, viscosity, gel strength, mechanical profile, thermal profile, and water vapor permeability, could be attributed to the addition of phenolics cross-linkers. The highest improvement was observed in gelatin added with basic tannic acid 10%. Gelatin cross-linked with basic tannic acid 10% had a moisture content of 9.24±0.14%, swelling index of 323±17%, degree of cross-linking of 69.99±0.84%, viscosity of 8.48±0.23 cP, gel strength of 151.5±6.9 Bloom, melting temperature of 213.5°C, tensile strength of 7.00±0.54 N.cm-2, elongation at the break of 114.08±14.63%, elastic modulus of 58.45±8.20 N.cm-2 and water vapor permeability of 0.57±0.07 g.mm.m-2.h-1. kPa-1. The qualities of tannic acid-cross-linked gelatin films and film-forming gel increased when manufactured under basic conditions in comparison to acidic or neutral conditions. Furthermore, increasing the quantity of tannic acid to 10% improved the overall characteristics as compared to non-cross-linked gelatin. In conclusion, tannic acid has the ability to cross-link the fish gelatin, thereby enhancing its qualities.